The Holocaust in Horserød - Bak, Sofie Lene (Journal of Scandinavian Cinema, 2012)
The rescue of the Danish Jews during the German occupation of Denmark is well known. This short article details how the recent find of an old home movie filmed by a convicted Danish Nazi perpetrator helps shed light on the much less familiar details of the Holocaust in Denmark.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qc2NhLjIuMy4yMTNfMQ